Varenicline Prevents LPS-Induced Inflammatory Response via Nicotinic Acetylcholine Receptors in RAW 264.7 Macrophages - Baris, Elif; Efe, Hande; Gumustekin, Mukaddes; Arici, Mualla Aylin; Tosun, Metiner (Frontiers in Molecular Biosciences, 2021)
Cholinergic anti-inflammatory pathway plays an important role in controlling inflammation. This study investigated the effects of varenicline, an α7 nicotinic acetylcholine receptor (α7nAChR) agonist, on inflammatory cytokines levels, cell proliferation and migration rates in lipopolysaccharide (LPS)-induced inflammation model in RAW 264.7 murine macrophage cells lines. Cells were treated with increasing concentrations of varenicline followed by LPS incubation for 24 hours. Prior to receptor-mediated investigations anti-inflammatory effects of varenicline on different cytokines and chemokines were investigated with a cytokine array. Nicotinic AChR-mediated effects of varenicline were investigated by using a non-selective nAChR antagonist mecamylamine hydrochloride and a selective α7nAChR antagonist methyllycaconitine citrate, TNFα, IL-1β, IL-6 levels were determined by ELISA in cell media 24 hours after the LPS administration and compared with those of dexamethasone. Cell proliferation and migration assays were monitored for 24 hours following by drug treatments using a real time cell analyzing system. Varenicline decreased LPS-induced cytokines and chemokines after 24 hours, Varenicline appeared to exert its effects mainly via α7nAChRs on TNFα, IL-6, IL-1β levels, similar to observations made in the dexamethasone treated group. Varenicline also inhibited LPS-induced cell proliferation and migration, possibly via the same receptor types. Our data suggest that varenicline inhibits LPS-induced inflammatory response by reducing the cytokine levels, cell proliferation and migration by activating α7nAChRs within cholinergic anti-inflammatory pathway.